Advancing the Water Footprint into an Instrument to Support Achieving the SDGs – Recommendations from the “Water as a Global Resources” Research Initiative (GRoW) - Markus Berger; Jazmin Campos; Mauro Carolli; Ianna Dantas; Silvia Forin; Ervin Kosatica; Annika Kramer; Natalia Mikosch; Hamideh Nouri; Anna Schlattmann; Falk Schmidt; Anna Schomberg; et al. (Water Resources Management, 2021)
The water footprint has developed into a widely-used concept to examine water use and resulting local impacts caused during agricultural and industrial production. Building on recent advancements in the water footprint concept, it can be an effective steering instrument to support, inter alia, achieving sustainable development goals (SDGs) - SDG 6 in particular. Within the research program “Water as a Global Resource” (GRoW), an initiative of the Federal Ministry for Education and Research, a number of research projects currently apply and enhance the water footprint concept in order to identify areas where water is being used inefficiently and implement practical optimization measures (see imprint for more information). With this paper, we aim to raise awareness on the potential of the water footprint concept to inform decision-making in the public and private sectors towards improved water management and achieving the SDGs.
Keywords: 330; water footprint; sustainable development goals